Mulheres obesas: características vocais e medidas fonatórias - Rossi, Débora Cardoso (2010)
INTRODUCTION: Grade III overweight is associated with health, respiratory and orofacial motility disorders. AIM: to describe the vocal characteristics and phonation measurements of a group of grade III overweight women. METHOD: The sample was composed of two groups, Study group (SG) composed of 30 women, in between 25 and 45 years of age, morbidly obese and candidates to bariatric surgery. The control group (CG) was selected by pairing with women of similar age groups, with no vocal signs and/or symptoms and with Body Mass Index (BMI) within normal values. The study was performed with volunteers from the city of Belo Horizonte (MG) and those subjects in the SG were followed by the Public health system in Belo Horizonte (MG). The recorded material was composed of sustained vowels /a/, /é/ e /i/ in the subject s habitual voice tone, chained speech composed of the months of the year and reading of a standard sentence. The perceptual-auditory evaluation was performed by judges and the acoustic analysis was done using software PRAAT. The mean fundamental frequency (f0), f0 variation, mean intensity, mean f0 of the segment /a/ of the word aves were extracted from the standard phrase and analyzed using the software. The same program was used to assess the mean f0 of the sustained vowel /a/. To obtain the maximum phonation time (MPT), the sustained emissions of /a/, /i/, /s/, and /z/ were measured. The data was analyzed using descriptive statistics, T-test and Mann-Whitney test. RESULTS: As far as the perceptual-auditory evaluation, for most subjects in the SG the results were: medium-high pitch, inadequate loudness levels (strong or weak), varied resonance types, though without balance, and GRBASI scale with General Grade (G) zero. The acoustic evaluation showed: mean f0 measurements above 204Hz and mean f0 in the segment /a/ of the word aves, below 204Hz. For MPT values: /s/ values were below 19.7s; /z/ values were below 18.5s; and vowels /a/ and /i/ were below 16.2 seconds. The results for the acoustic analysis for most subjects, in all speech samples for CG were: mean f0 values below 204Hz. All MPT values for the CG were higher than those in the SG. When comparing the SG and the CG, the following variables presented statistical significance: age group, weight, BMI, and in acoustics mean intensity and MPT. CONCLUSION: the grade 3 overweight women of the study group presented as vocal characteristics: medium-high pitch, inadequate loudness levels and unbalanced resonance. In acoustic evaluation the group presented higher fundamental frequency and lower maximum phonation times